Ms The Use of Physical Analysis in Assessing the Impact of Anthropogenic Climate Change: A Systematic Literature Review - Yuli Fitria (Journal of Climate Change Society, 2026)
Anthropogenic climate change is the primary cause of modern global warming and one of the greatest scientific challenges of the 21st century. This phenomenon is triggered by increasing concentrations of greenhouse gases (GHGs) such as CO₂, CH₄, N₂O, tropospheric ozone, and changes in aerosols that alter Earth's energy balance. This study aims to identify the latest scientific findings regarding the physical mechanisms that control anthropogenic warming and the Earth system's response to it. The method used is a Systematic Literature Review (SLR) of 30 primary research articles indexed by Scopus, Web of Science, Springer, MDPI, and Sinta (≥2) published in the period 2021–2025. The analysis is based on four research questions (RQs): the contribution of anthropogenic radiative forcing to Earth's Energy Imbalance, changes in atmospheric dynamics, the influence of climate feedbacks, and the response of Earth system components such as the ocean, cryosphere, biosphere, and atmosphere. The SLR results show that the increase in GHGs since the industrial era has resulted in significant positive radiative forcing, causing an increase in heat waves, changes in rainfall patterns, shifts in the jet stream and monsoon, and an intensification of ENSO variability. Furthermore, feedback mechanisms such as increased water vapor, decreased ice albedo, and cloud sensitivity amplify global warming, while carbon release from permafrost and decreased ocean absorption capacity increase long-term climate instability. This research confirms that anthropogenic climate change is an integrated process between the atmosphere, ocean, and biosphere, indicating the potential to reach tipping points. Strengthening climate physics modeling, improving the quality of observations, and integrating scientific findings into evidence-based mitigation policies are needed to prevent the acceleration of climate change in the future.